2014
DOI: 10.1074/jbc.m114.588640
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Plasminogen Binding and Delayed Activation Render γ′-Fibrin More Resistant to Lysis than γA-Fibrin

Abstract: Background: When compared with degradation of the predominant ␥ A -fibrin, lysis of variant ␥Ј-fibrin is delayed. Results: Thrombin-mediated fibrinopeptide B release is slower from ␥Ј-fibrinogen than from ␥ A -fibrinogen, resulting in delayed binding and activation of plasminogen. Conclusion: Delayed plasmin generation renders ␥Ј-fibrin resistant to lysis. Significance: The association between slower clotting and delayed lysis highlights the links between coagulation and fibrinolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…We also studied fibrin clots in the presence of 5% and 10% of RBCs by LSCM; however, the high number of Finally, we studied fibrinolysis of clots made with both fibrinogen variants ( Figure 7). In line with previous studies 21 , a significant increase in lysis time was observed for A ' compared with A A fibrin clots (15.82 ± 1.48 min vs. 10.54 ± 0.44 min, respectively; p = 0.0267).…”
Section: Relevant Was To Study the Micrographs Of Fibrin Clots From Asupporting
confidence: 92%
See 2 more Smart Citations
“…We also studied fibrin clots in the presence of 5% and 10% of RBCs by LSCM; however, the high number of Finally, we studied fibrinolysis of clots made with both fibrinogen variants ( Figure 7). In line with previous studies 21 , a significant increase in lysis time was observed for A ' compared with A A fibrin clots (15.82 ± 1.48 min vs. 10.54 ± 0.44 min, respectively; p = 0.0267).…”
Section: Relevant Was To Study the Micrographs Of Fibrin Clots From Asupporting
confidence: 92%
“…Fibrin clots formed in the presence of the fibrinogen ' variant are more resistant to fibrinolysis, due to reduced binding of plasminogen and tissue plasminogen activator, leading to reduced plasmin generation 21 . Fibrinogen ' variant is associated with a heterogeneous, non-uniform clot structure, with more branch points than clots formed by A chains 6,22,23 .In addition, ' fibrinogen binds to thrombin exosite II 24 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The ' fibers pack significantly less protofibrils and are less stiff than A fibers [14]. While ' clots are mechanically impaired, they are more resistant to proteolysis by plasmin than A clots due to impaired conversion of plasminogen to plasmin by tissue plasminogen activator on ' clots [15]. The significance of these effects for health and disease is less clear since increased levels of fibrinogen ' have been associated with coronary artery disease and myocardial infarction on one hand, while decreased levels have been associated with venous thrombosis on the other [16].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…However, this is the first time that the effects of fibrin(ogen) γ/ γ´ on endothelial cells are reported.The main finding of the present work is that fibrin(ogen) γ/ γ´ levels alter the secretion of the fibrinolytic components uPA and PAI 1 thus mimicking the effect of thrombin. In order to imitate physiological conditions or to reach pathological levels of fibrinogen γ/ γ´, this variant was mixed with fibrinogen γ/ γ, differing from previous studies where either purified[20][21][22]33] or recombinant[ 34,35] fibrinogen γ/ γ or fibrinogen γ/ γ´ were used.…”
mentioning
confidence: 99%